PERSEPSI MAHASISWA JURUSAN ILMU KOMUNIKASI UNIVERSITAS RIAU MENGENAI INFORMASI HOAKS VAKSIN COVID-19 DI MEDIA SOSIAL WHATSAPP - Ropida Auna; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The phenomenon of hoax news is increasingly troubling the public, especially during the Covid-19 pandemic in early 2020. As a new term, of course, many people are looking for information about Covid-19. This is what is used by irresponsible parties to spread hoaxes related to Covid-19. WhatsApp is the social media with the longest total duration used and also the social media that is considered the most worrying related to the spread of the Covid-19 hoax. This study aims to find out how the perception of Riau University Communication Science students regarding the Covid-19 vaccine hoax news on WhatsApp social media, what are the factors that affect perception, and how students' knowledge and understanding of hoax news. This research uses descriptive analysis with qualitative research types. Data collection uses observation, interview and documentation methods. The research subject focused on students majoring in Communication Sciences, Riau University class of 2021 who had received digital literacy classes. The key informants numbered 5 people, with the method of selecting informants using purpossive sampling. The data collection technique uses a fixed comparison analysis technique, while the data validity check uses the triangulation method. The results showed that the perception of Riau University Communication Science students class of 2021 regarding the Covid-19 vaccine hoax news was that most informants perceived that this phenomenon was disappointing and troubling because there are still many people who cannot distinguish which news is true and which is a hoax. All informants can recognize that the information they get is a hoax and do not believe the information. The factors affecting perception are divided into two, namely the experience factor and the perceived object. Students' knowledge and understanding can be concluded that students can describe the definition of hoax correctly, the characteristics of hoaxes, and how to overcome the phenomenon of the rise of hoaxes. The students considered that the rise of hoaxes in Indonesia could not be separated from the problem of low public literacy and lack of education about the hoax itself. Keywords: Perception, Hoax, Vaccine Covid-19, Students of Communication Science